Inkonsistensi Definisi Nelayan Kecil dalam Kerangka Hukum Indonesia: Studi Perbandingan Peraturan Perundang-Undangan - Muhammad Rinaldy Bima (SIGn Jurnal Hukum, 2023)
This study aims to examine and analyze the norm conflict regarding the definition of small fishermen in legislation at the same hierarchical level. This study uses normative legal research with the statute, conceptual, and comparative approaches. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show that there is a conflict of norms between Law Number 45 of 2009 with Law Number 7 of 2016 in defining small fishermen. Law Number 45 of 2009 refers to fishermen with a maximum vessel size of 5 GT, while Law Number 7 of 2016 refers to fishermen who use their own or others’ vessels with a maximum size of 10 GT. On the other hand, GT is a unit of measure agreed upon as the provisions of the Convention on the International Tonnage Measurement of 1969 in determining the vessel category. To eliminate norm conflict concerning the definition of small fishermen, the Government enacted the GR in Lieu of Law Number 2 of 2022. Fatally, GR in Lieu of Law Number 2 of 2022 raises ambiguity which shows the definition of small fishermen is increasingly unclear. Therefore, it is recommended that the House of Representatives initiate amendments to Law Number 7 of 2016 and GR in Lieu of Law Number 2 of 2022. These amendments must accommodate a more specific indicator regarding vessel size, aligned with the provisions in Law Number 45 of 2009. These steps are expected to create greater legal clarity and certainty for small fishermen and provide improved guidance for all stakeholders in the maritime and fisheries sector.